PENGGUNAAN PIRANTI PENDUKUNG UNTUK MELEMBUTKAN UJARAN: SEBUAH KASUS KESANTUNAN BAHASA BALI - Seken, I Ketut (Universitas Pendidikan Ganesha, 2013)
This article discusses a case of politeness in Balinese referred to as softening strategies using supportive moves. The data used were obtained through non-participant observation on the peparuman adat in the village of Dawan Kelod, Subdistrict of Dawan, Klungkung Regency, and were analyzed by means of a flow model (Miles & Huberman, 1984) and Brown & Levinson’s (1987) theory of politeness. It was found that five types of supportive moves were used in the softening strategies, namely, preparator, imposition minimizer, grounder, alerter, and disarmer. The conclusion arrived at was that the use of the strategies conforms to the universal pattern postulated by Brown & Levinson (1987) but the realization reflects Balinese cultural values.Key Words: supportive moves, softening strategies